ANALISIS OPTIMALISASI INTEGRASI BIM (TEKLA STRUCTURES) UNTUK DESAIN CIVIL STRUCTURAL DAN KOORDINASI PADA PROYEK EPC OIL & GAS - Edison Hatoguan Manurung; Sumadulloh Sumadulloh (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
the integration of Tekla structural models with plant design platforms such as AVEVA E3D and Intergraph Smart 3D (SP3D), along with model federation in Autodesk Navisworks, is employed to facilitate clash detection, staged 30–60–90% model reviews, and multidisciplinary decision‑making. The study adopts a descriptive research design using a literature review approach, complemented by the author’s reflective experience as a civil–structural Tekla Designer during the DED phase, to formulate a conceptual BIM integration model within the framework of a Common Data Environment (CDE), ISO 19650 standards, and Level of Development (LOD). The findings suggest that consistent LOD definition, robust information governance in the CDE, disciplined management of clash tests in Navisworks, and a structured 30–60–90% model review scheme are critical in improving multidisciplinary coordination and reducing rework during DED. The proposed conceptual model is expected to provide an initial reference for practitioners and academics in designing BIM‑based workflows for Tekla–E3D/SP3D–Navisworks integration in EPC oil and gas projects.